Effect of Extraction and Centrifugation on Caffeine Levels in Urine of Robusta Coffee Drinkers Using the Method of Uv-Vis Spectrophotometry - Anik Eko Novitasari; Nikmatul Fitriyah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Caffeine is a heterocyclic alkaloid compound in the methylxanthine group that has a bitter taste that works as a mild diuretic and psychoactive stimulant. These compounds are naturally found in more than 60 types of plants, including coffee plants. Coffee is known as a drink that has a high enough caffeine content. Caffeine content in robusta coffee raw beans is higher than Arabica coffee which is only about 1.2%. The content of caffeine in the body is broken down in the liver by the enzyme cytochrome P-450 into metabolic 3-dimethylxanthin which is then excreted in the urine. Analysis of caffeine in urine was carried out quantitatively by means of UV-Vis Spectrophotometry. The analysis process is carried out by extraction and centrifugation. Based on this study, a study was conducted to determine the differences in extraction and centrifugation methods on caffeine levels in the urine of robusta coffee drinkers using the UV-Vis spectrophotometric method. The results were analyzed using the Paired T-Test through SPSS. The results showed that there was significant difference in the levels of caffeine extracted and centrifuged in the urine of robusta coffee drinkers using the UV-Vis Spectrophotometry method. The caffeine content in the urine sample was obtained with the lowest extraction at 29.60 ppm and the highest caffeine content at 50.18 ppm. Meanwhile, in urine samples by centrifugation, the lowest caffeine content was 35.71 ppm and the highest caffeine content was 50.45 ppm.